2018
DOI: 10.1007/s41782-018-0036-y
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Sleep Quality and Subjective Fatigue in Night-Shift Nurses with Good and Poor Sleep

Abstract: Purpose This study aimed to explore the association between sleep quality and subjective fatigue in nurses who performed rotational-shift work. Methods A cross-sectional survey was conducted and included nurses working day and night shifts (n = 35) at Toyama University Hospital in Japan. To examine the influence of sleep quality on subjective fatigue, participants were categorized as poor (n = 23) or good (n = 12) sleepers. They assessed their own sleep status using the St Mary's Hospital Sleep Questionnaire a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Circadian adaptation is difficult to deal with during short‐term rotating shift work (McKenna & Wilkes, ). Thus, nurses who are in rotating shift work need to increase their sleep duration, especially “before or after a night shift” and following a day shift (Ichiba et al, ). Bright‐light exposure may be effective in resetting circadian rhythms to follow sleep schedules imposed by rotating shift work.…”
Section: Recommendations For Handling Shift Nurses Sleep Problemsmentioning
confidence: 99%
“…Circadian adaptation is difficult to deal with during short‐term rotating shift work (McKenna & Wilkes, ). Thus, nurses who are in rotating shift work need to increase their sleep duration, especially “before or after a night shift” and following a day shift (Ichiba et al, ). Bright‐light exposure may be effective in resetting circadian rhythms to follow sleep schedules imposed by rotating shift work.…”
Section: Recommendations For Handling Shift Nurses Sleep Problemsmentioning
confidence: 99%
“…The majority of previous works [23][24][25][26][27][28] investigated sleep quality using a monthly survey of PSQI [82]. However, in this study we used the daily survey of DUCSS [81] for assessing each individual's sleep quality every night as a step toward early detection and early intervention.…”
Section: Discussionmentioning
confidence: 99%
“…A wide range of studies explore the relationship between sleep and health issues such as obesity [17], weakened immune system [18], Parkinson's disease [19,20], mortality [5], heart failure [21], and cancer [22]. Additionally, the relationship between sleep and performance of students [23], athletes [24], and workers [25] have been correlated. In this section, we review some of these massive studies from three different aspects: caregivers' sleep problems, sleep architecture, and its measurement tools.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, there are individual differences in the sensitivity to shift work among shift workers (17). Our recent study on nurses found that the subjective fatigue at wake time while they worked the day off to day shift and day shift to day shift was significantly higher in poor sleepers than in good sleepers (18). These results suggest that certain physiological factors during sleep might be related to individual differences (i.e., good vs. poor sleepers), which might in turn affect subjective fatigue at wake time.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we hypothesized that fatigue at wake time might be ascribed to “non-restorative sleep,” which is linked to specific changes in EEG and HRV parameters in poor sleepers. To investigate this issue, we analyzed the relationship between subjective fatigue at wake time and the physiological parameters during sleep in shift nurses, in the same situation as in our previous study (18) (i.e., the nurses worked the same shift schedule and slept at home). For this purpose, the physiological data were recorded from the nurses at their home while they worked similar shift work schedules.…”
Section: Introductionmentioning
confidence: 99%